2000
DOI: 10.1111/j.1751-0813.2000.tb11754.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of multilocus enzyme electrophoresis to distinguish clinically important strains of Staphylococcus intermedius from the skin of dogs

Abstract: The small difference in genetic diversity between isolates from the skin and mucosa of healthy dogs and isolates from various diseases, as well as the presence of the majority of isolates in two ETs, is consistent with the role of S intermedius as an opportunistic pathogen. The confinement of all Staphylococcal Scalded Skin Syndrome isolates within one ET is confirmation of this entity as a distinct disease of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…These results are consistent with the known role of S. intermedius as an opportunistic pathogen [4,17]. The epidemiologic analysis of the isolates from different sites on the same healthy and diseased dogs suggested that elimination of S. intermedius from healthy carrier sites by disinfection in addition to elimination from lesions would be worthwhile in the treatment of staphylococcal skin disease including otitis externa in dogs.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…These results are consistent with the known role of S. intermedius as an opportunistic pathogen [4,17]. The epidemiologic analysis of the isolates from different sites on the same healthy and diseased dogs suggested that elimination of S. intermedius from healthy carrier sites by disinfection in addition to elimination from lesions would be worthwhile in the treatment of staphylococcal skin disease including otitis externa in dogs.…”
supporting
confidence: 77%
“…There are several reports on the population sizes and frequency of the organism at these carrier sites in healthy dogs [2,3,9,22]. Nevertheless, comparison of the characteristics of isolates from different sites in individual healthy dogs has not been studied sufficiently [4]. The organism has frequently been cultured from other body sites besides lesion sites in diseased dogs, but information on the clonal relationship between the organisms in the lesions and those in the nose or skin is lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report states that exfoliative toxin A, produced by Staphylococcus aureus in humans with bullous impetigo and staphylococcal‐scalded‐skin syndrome, also targets desmoglein 1 37 . None of our cases exhibited clinical or histological signs consistent with these diseases, as reported in dogs 38–40 …”
Section: Discussionsupporting
confidence: 57%
“…Ribotyping subsequently identified 11 types (16), and various methods confirmed this strain diversity in diseased and healthy dogs (2,9,24,26). However, canine S. intermedius strains appear to compose a homogeneous population, and there is no clear link between isolates' genetic profiles and their pathogenicity (2,3,16,23,26). Human S. intermedius strains have rarely been characterized (22,23), but they resemble canine isolates.…”
Section: Staphylococcus Intermedius Was Described By Hajek In 1976mentioning
confidence: 99%